A rare case of IgE kappa monoclonal gammopathy of undetermined significance identified in a Swedish female. (1st September 2021) - Fager Ferrari, Marcus; Lemonakis, Konstantinos; Förnvik Jonsson, Magnus
Abstract: Monoclonal gammopathies involving immunoglobulin E (IgE) is a very rare phenomenon, with less than 70 cases being previously described in the literature. The IgE monoclonal gammopathies include malignant plasma cell disorders such as IgE multiple myeloma (MM), as well as the associated premalignant condition IgE monoclonal gammopathy of undetermined significance (MGUS). We report a case of a 41-year-old woman presenting with an IgE kappa monoclonal protein following routine laboratory testing. Serum protein electrophoresis (SPEP) initially showed a monoclonal protein in the beta-2 fraction, at an estimated concentration of <4 g/L. Subsequent serum immunofixation electrophoresis (SIFE) including antisera to Ig heavy chains delta and epsilon confirmed the presence of an IgE kappa monoclonal protein. Analysis of serum free light chains (FLCs) showed increased levels of kappa FLC, resulting in an abnormally elevated kappa/lambda FLC ratio. No Bence–Jones proteinuria was present. Bone marrow aspiration showed 6% plasma cells, and no sign of myeloma-associated end-organ damage was evident. Consequently, the patient was diagnosed with IgE kappa MGUS. In the present report, the clinical characteristics of the patient are compared to previous descriptions of IgE monoclonal gammopathy. The report further emphasizes the importance of considering the presence of monoclonal IgD or IgE when SIFE shows a clear band positive for a light chain but is negative for Ig heavy chains gamma, alpha and mu.